The emergence of phonological dispersion through interaction: an exploratory secondary analysis of a communicative game - Roberts, Gareth; Clark, Robin (Frontiers in Psychology, 2023)
Why is it that phonologies exhibit greater dispersion than we might expect by chance? Roberts and Clark (2020) investigated this using a non-linguistic communication game in which pairs of participants sent each other series of colors to communicate a set of animal silhouettes. They found that above-chance levels of dispersion, similar to that seen in vowel systems, emerged as a result of the production and perception demands acting on the participants. However, they did not investigate the process by which this dispersion came about. Here we present a secondary analysis of their data in which we shed light on how participants approached the communication task, how dispersion emerged, and what convergence looked like. We found in particular that dispersion was not planned from the start but emerged as a large-scale consequence of smaller-scale choices. This sheds light on the role of interactive processes in mediating between human minds and the distribution of features across the world's languages.